Popularitas Gamelan Gong Kebyar Dalam Arena Pertarungan Kekuasaan Gamelan Bali - Kadek Rismandika (SELONDING, 2018)
Gong kebyar is the most popular Balinese gamelan ensemble. Gong kebyar is a new class of Balinese gamelan created between 1910 and 1915 in the north of Bali. The popularity of gong kebyar is used as a medium in the arena of power struggles. The analysis of this study uses the ethnomusicology point of view in discussing gong kebyar in the context of Balinese culture and sociology discipline to discuss gong kebyar in social scope critically. "Kebyar" refers to the Bourdieu power theory that used as a cultural capital in the arena of Balinese gamelan power struggle. Gong kebyar through cultural capital of the symbolic value "kebyar" gained dominance in the arena of Balinese gamelan power struggle. Balinese gamelan outside gong kebyar experiencing changes in the form of “tabuh gong” is the inclusion of the “tabuh gong” which is the identity of musical character of Gong kebyar. Keywords: gong kebyar, kebyar, cultural capital, Balinese gamelan.